Infant mortality and risk factors in Nigeria in 2013−2017: A population-level study - Shobiye, Damilola M.; Omotola, Ayomide; Zhao, Yueming; Zhang, Jianrong; Ekawati, Fitriana M.; Shobiye, Hezekiah O. (Elsevier, 2022)
Background Globally, over the past two decades, many countries have significantly reduced the rate of infant mortality. Yet, in Africa, Nigeria remains one of the countries with the highest infant mortality rate (IMR). Methods We conducted a population-level study using the 2018 Nigeria Demographic Health Survey (NDHS). A total of 41,668 household data were analyzed retrospectively. The association between each exposure and infant mortality was analyzed in logistic regression models (independently adjusted by demographic and socioeconomic status variables) and confirmed by the multiple comparisons analysis. Findings The overall IMR of 2013−2017 was 61.5 (95% CI 58.0, 65.3) per 1000 live births. In general, the North-West and North-East regions had the highest IMR, whereas the South-West, South-East and South-South regions had the lowest IMR. The regression analysis found women who delivered their babies at the age <=18 years old (odds ratio (OR): 1.37 [1.17, 1.62]), had religion of Islam (OR: 1.35 [1.10, 1.65]), no ANC visit (OR: 1.69 [1.21, 2.35]), >4 ANC visits (OR: 1.70 [1.23, 2.34]), ANC not at home or skilled provider (0.40 [0.35, 0.46]) and the babies as the first child (OR: 1.23 [1.07, 1.42]) to be associated with higher IMR. Interpretation Our findings imply that Nigeria is not on track to achieving the SDG target of reducing child mortal- ity by 2030. Sustainable interventions are urgently needed to address the challenges for women of reproductive age, particularly those that are living in the rural areas and Northern regions, having limited/no access to health care/ skilled providers, and delivered their first child.